Powers of Division: "Smart" Spaces as Controlling Workplace Activity Fragmentation. Issue 2 (3rd March 2020) - Stiles, Jonathan; Andrews, Clinton
Abstract : In this article we argue that "smart" work spaces are created through access to wireless networks and mobile cloud computing collaboration software. Yet the power relations embedded in these overlapping physical and cyberspaces function to control the spatial and temporal fragmentation of related work activities. Through a review of the literature, we first describe how scholars have considered the relationship between space, technology, and the workplace and how conceptions of work activity fragmentation developed over time in relation to computing technology. We provide data from the American Time Use Survey to show the extent of work activity fragmentation among workers in the United States, finding that spatial fragmentation is more prominent among knowledge workers in large metropolitan areas. Drawing on original interview and observation data in the New York metropolitan area, we then describe both the cyberspaces of work enabled by mobile cloud collaboration software and the physical spaces of work opened up by the availability of wireless networks in diverse locations. Finally, we consider how the exercise of power and control in these overlapping physical and cyberspaces can either enable or prevent the fragmentation of work activities at multiple points. Key Words: activity fragmentation, cyberspace, information and communication technology, power relations, smart space.